Cystosarcoma phyllodess. Case presentation - Lidia Torres Ajá (Medisur)
A 12 year-old patient is presented, with tumor of the left breast of 11,7 cms, of quick growth, without another accompanying sintomatology, which was diagnosed as cystosarcoma phyllodess benign. In the twenty-five years of existence of our hospital, it is the first tumor phyllodes detected in girl, for that is considered a curious and interesting case that can enrich the experience of other professionals of the health.